2012
DOI: 10.1002/chem.201202192
|View full text |Cite
|
Sign up to set email alerts
|

Can an Amine Be a Stronger Acid than a Carboxylic Acid? The Surprisingly High Acidity of Amine–Borane Complexes

Abstract: The gas-phase acidity of a series of amine-borane complexes has been investigated through the use of electrospray mass spectrometry (ESI-MS), with the application of the extended Cooks kinetic method, and high-level G4 ab initio calculations. The most significant finding is that typical nitrogen bases, such as aniline, react with BH(3) to give amine-borane complexes, which, in the gas phase, have acidities as high as those of either phosphoric, oxalic, or salicylic acid; their acidity is higher than many carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 62 publications
3
22
0
Order By: Relevance
“…42 Other Lewis acids different from beryllium, as boron or aluminum, can also induce significant acidity enhancements. [36][37][38][39] Similar closed-shell interactions as those described for beryllium compounds are found in boranes BX 3 and alanes AlX 3 , compounds that suffer a significant distortion when forming dative bonds with Lewis basis as it was previously shown on preceding sections. Therefore, the intrinsic acidity of phosphine is notably different from that of phosphine-boranes (seventeen orders of magnitude greater in terms of the corresponding equilibrium constant), but the most relevant finding is that these theoretical predictions are fully ratified by the experimental evidence.…”
Section: Effects On the Intrinsic Properties Of The Interacting Monomerssupporting
confidence: 73%
See 2 more Smart Citations
“…42 Other Lewis acids different from beryllium, as boron or aluminum, can also induce significant acidity enhancements. [36][37][38][39] Similar closed-shell interactions as those described for beryllium compounds are found in boranes BX 3 and alanes AlX 3 , compounds that suffer a significant distortion when forming dative bonds with Lewis basis as it was previously shown on preceding sections. Therefore, the intrinsic acidity of phosphine is notably different from that of phosphine-boranes (seventeen orders of magnitude greater in terms of the corresponding equilibrium constant), but the most relevant finding is that these theoretical predictions are fully ratified by the experimental evidence.…”
Section: Effects On the Intrinsic Properties Of The Interacting Monomerssupporting
confidence: 73%
“…37 This acidity enhancement is even larger when the phosphine is replaced by the corresponding amine, and the acidity gap between aniline-borane and the free aniline is 136 kJ mol -1 . 39 It is worth noting that the acidity enhancement is also larger for phosphine-alanes 38 than for the corresponding phosphine-borane analogues, an unexpected result since boranes should be, in principle, better Lewis acids than alanes. Once again, the reason behind this phenomenon is the greater stabilization of the deprotonated phosphine which is significantly larger in complexes with alanes than in complexes with boranes.…”
Section: Effects On the Intrinsic Properties Of The Interacting Monomersmentioning
confidence: 96%
See 1 more Smart Citation
“…This theoretical model has been proven to provide reliable results for similar complexes when compared with experimental values and high-level ab initio methods such as G3 and G4 theories. 30,32 Nevertheless we have assessed its reliability to reproduce the gas-phase acidities of the systems under investigation in this paper using as a reference G4 theory 40 calculations, for a suitable set of benchmark cases. Obviously, the B3LYP/6-311+G(3df,2p)// B3LYP/6-31+G(d,p) model is not applicable to Sb containing compounds, for which the aforementioned basis sets are not available, and where relativistic effects cannot be considered negligible.…”
Section: Computational Detailsmentioning
confidence: 99%
“…30,32 These acidity enhancements are even larger when the Lewis acid is a beryllium derivative, 34 an electron deficient system, that as borane or alane behaves as a very strong Lewis acid. Some evidence seems to indicate that the effect depends on the nature of the Lewis base active site, since in general it has been found that the acidity enhancement is about twice as large in amine-boranes 32 than in phosphine-boranes. 30 There are four aims of this paper: (i) to investigate the acidity trends down group 15 of elements, more specifically when the heteroatom is directly bonded to an unsaturated moiety, in particular to a vinyl or to an ethynyl group, (ii) to analyze the effect that the association of these compounds either with BH 3 or BeH 2 has on their intrinsic acidities, (iii) to explore whether reactivity changes are directly related to the deformation of the base, the acid or both, and (iv) to explore the possibility that this association may lead to a change in the nature of the group losing the proton.…”
Section: Introductionmentioning
confidence: 99%